Vertical Sprawl in the Australian City: Sydney's High-rise Residential Development Boom. Issue 1 (2nd January 2020) - Troy, Laurence; Randolph, Bill; Pinnegar, Simon; Crommelin, Laura; Easthope, Hazel
ABSTRACT: This paper examines the spatial implications of Sydney's vertical expansion over the past decade. Enabled by a partnership between market forces and strategic planning policy, the data indicate that the city's high-density development boom has been primarily shaped by economic viability concerns, driving a spatial policy shift to better align better with market forces. The paper concludes that in the absence of more comprehensive housing and urban policies, housing supply ultimately remains primarily a numbers game, delivered where the market finds it most profitable to do so, with planning acting to facilitate development in these locations.